The Effect of Education of Breast Self Examination on Knowledge, Attitude and Practice of Health-care Volenteers in Gachsaran - Z. Shahvari; L. Gholizade (Iran University of Medical Sciences, 2006)
Background & Aim: Breast cancer is one of the most important causes of women's mortality, in the world wide. Breast self examination (BSE) is a method that often leads to detect breast cancer in early stage. Therefore, health care team, such as health care volunteers have an important role for traning BSC to women. The aim of the study was to determine the effect of education of breast self- examination on knowledge, attitude and practice of health care volunteers, in Gachsaran, in 2005. Material & Method: A quasi-experimental study was conducted, in which the data were collected by a case-record form and a check-list. The study sample consisted of 53 health mediators by census method from five health care centers (one in rual area) in Gachsaran.   Results: The sign test showed a statistically significant increase in the mean of knowledge scores at post-intervention compared to pre-intervention (P=0.000). The result of wilcoxone test showed a significant increase in the mean scores of attitude at posttest compared to pre-test (P=0.021) too. Also the results of kruskalwallis test showed a significant increase in the mean of BSE practice at post-test compared to pre-test (P=0.000). The literacy level of the study subjects had a significant influence on BSE knowledge level at post-test (P=0.015). In addition, the kruskall wallis test showed the mean seores of BSE practice in women with the history of breast pain was significantly high (P=0.019). Conclusion: To sum up, educating health eare volunteers could lead to increase the in levels of knowledge, attitude and practice of BSE. Therefore, it is recommended that to establishe practical BSE classes for all women in the community educating health care voluntcers would be neccessary.